Psicanálise e biopolítica - Michel Foucault e a psicanálise na história da sexualidade - V.I - A vontade de saber - Teshainer, Marcus Cesar Ricci (2005)
In the beginning it was necessary to delimit what one can understand as psychoanalysis as, even in Foucault s book, it may be seen under diverse approaches. Therefore an investigation has been carried out going over all of Foucault s pathway to check the different ways this author approches psychoanalysis in its diverse theoretical moments. Three distinct approuches can be clearly made out all over Foucault s work; at first psychoanalysis is seem as closely related to discourse, then the discussion turns to Freud as author and finally in Story of Sexuality: An Introduction psychoanalysis is seen as a dispositive. The concept of psychoanalysis to wich Foucault refers to in this book is the one related to practice, to exercise, undesrtood as an instituition of knowledge. In order to contextualize historically the different discussions throughout Foucault s work a brief study has been carried out concerning his relationship to the structuralism which was emerging in France as he was publishing his studies. In a second moment-the chosen work already being analyzed-the concepts which support biopolitics have been studied regarding their relationship to discipline and the government of populations-two points which provide a basis to this concept. After being analyzed the questions on biopolitics were related to the point of view presented by Foucault in Story of Sexuality: An Introduction about psychoanalysis and it has been attenpted to examine which consequences this relationship brings to psychoanalysis as well to biopolitics. Finally resuming the questions reised above and connecting them to each other it has been attempted to point out which aspects of psychoanalysis are linked to biopolitics and wich are not